Analisa Perbandingan Metode SMART dan SAW dalam Rekomendasi Rumah Kost di Wilayah Perbatasan - Candra Gudiato; Mira Mira; Noviyanti P (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The selection of a boarding house is an important decision that cannot be made arbitrarily because a boarding house is a place to rest after a day of activities outside, whether for work or studying. The border area differs slightly from other areas, adding complexity to the list of considerations in searching for a boarding house. To address the varying preferences, a Decision Support System (DSS) can be utilized, assisting individuals in making better decisions when selecting a boarding house. A DSS is designed to help decision-makers analyze and compare various alternatives based on predetermined criteria. This research was conducted to analyze the effectiveness of the SMART method and the SAW method commonly used in DSS in providing recommendations for the best boarding house according to user preferences. The results showed that both the SMART method and the SAW method produced similar and consistent results, with both placing